The importance of human capital perspective in the Learning Management System (LMS) decision making process at universities - Norhaiza Khairudin,; Rozainee Khairudin,; Mohd Noor Abdul Hamid,; Hancock, Philip; McGill, Tanya; Zainah Ahmad Zamani, (Penerbit Universiti Kebangsaan Malaysia, 2016)
This research examined how managers in universities incorporate non-financial measures in their Learning Management Systems decision-making processes and particularly focused on the importance of the Human Capital perspective in LMS decision making processes. A mixed-methods approach to data collection was used involving both interviews and questionnaires. The qualitative data from the interviews were coded and analysed. A descriptive coding method using thematic analysis was used for the data coding. The qualitative data were analysed using an inductive approach where the categories of criteria and indicators were not determined before the interview. The participants in this research were five members of LMS decision-making teams at two different universities in Australia and 24 participants from different universities in Malaysia who were involved in LMS decision- making pro-cesses at their universities. The results of this research indicated that there was substantial support for using a multi-dimensional decision making model among IT decision makers at universities, particu-larly the Human Capital perspective and they believed that Human Capital measures are important and should be considered in a LMS decision making process.The research has both implications for theory and for practitioners where it contributes to the knowledge on LMS decision making in univer-sities and IT decision making in general, and also in improving actual decision making practices.